Did You Get Your Shots? Experimental Evidence on the Role of Reminders - Matías Busso; Julián Cristia; Sarah Humpage (Inter-American Development Bank (IDB), 2015)
Many families fail to vaccinate their children despite the supply of these services at no cost. This study tests whether personal reminders can increase demand for vaccination. A field experiment was conducted in rural Guatemala in which timely reminders were provided to families whose children were due for a vaccine. The six-month intervention increased the probability of vaccination completion by 2.2 percentage points among all children in treatment communities. Moreover, for children in treatment communities who were due to receive a vaccine, and whose parents were expected to be reminded about that due date, the probability of vaccination completion increased by 4.9 percentage points. The cost of an additional child with complete vaccination due to the intervention is estimated at about 7.50.
hdl:11319/6944
Keywords: I14; O15; C93; 330; Vaccination; Reminders; Field experiment; Guatemala